The role of digital transformation in improving characteristics of the quality of accounting information: An analytical study of the opinions of accounting staff at the Northern Technical University in Mosul: The role of digital transformation (NTU journal for Administrative and Human Sciences (JAHS), 2023)
The research aims to explore the extent to which private bank departments, the research sample, carry out human resource management practices and fulfill their obligations specified in the psychological contract towards workers and the impact of this on their job satisfaction, considering the fulfillment of the psychological contract as a mediating variable between those practices and job satisfaction, data was collected through a questionnaire for a sample (52) of the total workers in the research community, whose number is estimated at (180), data analyzed by statistical program (SPSS.V25) to describe the variables and test the research hypotheses, where mean, correlation and regression used for that, research reached a set of conclusions, including human resource management practices can be a good predictor of the extent to which the psychological contract is fulfilled, and that the latter is considered a variable with a total mediation between human resource management practices and job satisfaction. And some suggestions, including managing private bank must must clarify the employee's duties and expectations accurately, and what the organization will offer in return, during employment interviews. And it should not set expectations or make unrealistic promises and pledges that are difficult to fulfill and, when violated, may lead to dissatisfaction.